Proceedings of the 1st ACM SIGCAS Conference on Computing and Sustainable Societies 2018
DOI: 10.1145/3209811.3209819
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Access, and Decision-Making

Abstract: In resource-constrained economies, lack of financial participation prohibits women's economic empowerment and opportunities to improve circumstances. With the advent of Digital Financial Services (DFS), a growing emphasis has been placed on the possible positive impact of DFS on lives of individuals. However, for people to understand, adopt, and use DFS, they require certain prerequisites and enablers. In this paper, we use a mixed methods approach to analyze the gendered barriers in the readiness for and adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Field, Pande, Rigol, Schaner, and Troyer Moore (2021)study in India shows that strengthening women's financial control boosts their labor supply and challenges gender norms. Ibtasam et al (2018)examine gender roles and financial inclusion in Pakistan, revealing that socio-cultural and gender norms restrict women's access to financial services. Additionally, a study by Khan and Ullah (2021) in Pakistan emphasizes the positive impact of financial inclusion on women entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Field, Pande, Rigol, Schaner, and Troyer Moore (2021)study in India shows that strengthening women's financial control boosts their labor supply and challenges gender norms. Ibtasam et al (2018)examine gender roles and financial inclusion in Pakistan, revealing that socio-cultural and gender norms restrict women's access to financial services. Additionally, a study by Khan and Ullah (2021) in Pakistan emphasizes the positive impact of financial inclusion on women entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, increasing women's access to digital financial services (DFS), such as digital payment systems and mobile financial services, will help minority groups like women to make their own decisions regarding spending, savings, and financial risk [22]. A study on developing countries like Pakistan, where cultural, religious, and security concerns are evident, shows that decision making and own behalf action taking will help women access fintech services regardless of the availability of infrastructure and technology [23]. A scholarly study in Bangladesh showed that during the COVID-19 pandemic, regardless of gender among these communities, technology, and technology based services such as digital financial services adoption increased in day-to-day work and financial work [25].…”
Section: Community Engagement and Risk Communication (Rcce)mentioning
confidence: 99%
“…Ibtasam et al [64] have established that in resource-constrained nations, a lack of financial participation harms women's economic empowerment and opportunity to better their conditions. Hendriks [17] posited that financial inclusion significantly impacts millions of women's lives and livelihoods globally and is a key tenet of its strategy for women's economic empowerment.…”
Section: Financial Inclusion and Women Empowermentmentioning
confidence: 99%